2004
DOI: 10.1038/sj.onc.1207316
|View full text |Cite
|
Sign up to set email alerts
|

Generating mutations but providing chemosensitivity: the role of O6-methylguanine DNA methyltransferase in human cancer

Abstract: O 6 -methylguanine DNA methyltransferase (MGMT) is a key enzyme in the DNA repair network. MGMT removes mutagenic and cytotoxic adducts from O 6 -guanine in DNA, the preferred point of attack of many carcinogens (i.e. methylnitrosourea) and alkylating chemotherapeutic agents (i.e. BCNU, temozolamide, etc.). Hypermethylation of the CpG island located in the promoter region of MGMT is primarily responsible for the loss of MGMT function in many tumor types. The methylation-mediated silencing of MGMT has two conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
190
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(199 citation statements)
references
References 87 publications
(82 reference statements)
3
190
0
6
Order By: Relevance
“…Ten percent of colorectal tumours have simultaneous silencing of both genes, and this phenomenon confers 44 resistance to cell death, producing a high incidence of mutation. Although tumours with methylated MGMT are more sensitive to the apoptotic effects of alkylating agents, it has been reported that Mgmt À/À mice with a loss of MLH1 expres- DNA repair genes in monoclonal gammopathies P Martin et al sion 45,46 are as resistant to alkylating drugs as are wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ten percent of colorectal tumours have simultaneous silencing of both genes, and this phenomenon confers 44 resistance to cell death, producing a high incidence of mutation. Although tumours with methylated MGMT are more sensitive to the apoptotic effects of alkylating agents, it has been reported that Mgmt À/À mice with a loss of MLH1 expres- DNA repair genes in monoclonal gammopathies P Martin et al sion 45,46 are as resistant to alkylating drugs as are wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most plausible candidates for a gene whose inactivation may initiate carcinogenesis is MGMT, which codes for a protein that removes alkyl adducts from the O6 position of guanine (5). Loss of MGMT function will give rise to a mutator phenotype, as alkylation damage from a variety of environmental sources is a common occurrence and as alkylated guanine is likely to mispair with thymine during DNA replication.…”
mentioning
confidence: 99%
“…Tumors displaying MGMT promoter methylation are more sensitive to the killing effects of the nitrosourea-type alkylating drugs used in chemotherapy. 28 In support of the MGMT role in malignant conversion, Becker et al 16 have shown recently that overexpression of MGMT in mouse skin reduced the MNU-induced conversion from papillomas to carcinomas by 4-fold. Baylin and Herman 24 have reviewed the role of several genes regulated by CpG methylation and stressed that ''.…”
Section: Discussionmentioning
confidence: 97%
“…28 In the development of human colon cancer, methylation of MGMT, an early step in the process, is associated with the subsequent development of G-A transition mutations in Ki-ras. 7 In pancreatic carcinomas, however, there was no association between a high rate of Ki-ras mutations and MGMT promoter methylation.…”
Section: Discussionmentioning
confidence: 99%